Pengelolaan Dana Zakat Produktif untuk Pemberdayaan Masyarakat pada LAZ El-Zawa - M. Salman Firmansyah; Indah Yuliana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this study was to find out how to manage zakat funds effectively in LAZ EL-ZAWA to increase community capacity. The method used by the researcher uses qualitative research and descriptive methods to describe the data obtained from the field, then draws conclusions from the research conducted. In this study, there are two sources of data used, namely, primary data and secondary data where primary data is generated through direct interviews with parties related to research (researchers) and secondary data is obtained from reading sources and various other sources. The result is that at LAZ EL-ZAWA there are two mechanisms used by el-zawa in collecting zakat funds, the first is a personal approach and an institutional approach. There are two objects for distributing productive zakat in el-zawa, the first at the community level by providing capital assistance to MSMEs The second need is to allocate productive zakat funds to students of UIN Maulana Malik Ibrahim by providing scholarships